Are there any common effects in preclinical models of micro- and nanoplastic (MNP) exposure? A systematic review - Diego Ruiz-Sobremazas; Pablo Jiménez-López; Mario Ruiz Coca; Miguel Morales-Navas; Cristian Perez-Fernández; Maria del Mar López-Rodríguez; Tania Romacho; Fernando Sánchez-Santed (Journal of Hazardous Materials, 2026)

Long-term impact of oral gestational PM10 exposure on morris water maze performance and hippocampal gene expression - Ruiz-Sobremazas Diego; Coca Mario; Morales-Navas Miguel; Nerea Rios Nieto; Rodulfo-Cárdenas Rocío; Colomina Maria Teresa; López-Granero Caridad; Sanchez-Santed Fernando; Perez-Fernandez Cristian (Environmental Toxicology and Pharmacology, 2025)

The effects of oral gestational particulate matter 10 exposure: Insights into neurodevelopmental milestones, inhibitory control, adult sociability, and object recognition - Diego Ruiz-Sobremazas; Mario Coca; Miguel Morales-Navas; Rocío Rodulfo-Cardenas; Caridad Lopez-Granero; Maria-Teresa Colomina; Cristian Perez-Fernandez; Fernando Sanchez-Santed (NeuroToxicology, 2025)

Neurodevelopmental consequences of gestational exposure to particulate matter 10: Ultrasonic vocalizations and gene expression analysis using a bayesian approach - Diego Ruiz-Sobremazas; Mario Ruiz Coca; Miguel Morales-Navas; Rocío Rodulfo-Cárdenas; Caridad López-Granero; Maria Teresa Colomina; Cristian Perez-Fernandez; Fernando Sanchez-Santed (Environmental Research, 2024)

Virus Incidence Associated with Native Potato Yield in Microcenters of Potato Genetic Diversity of Bolivian - Mario Coca Morante; Evelyn Coca Salazar; Javier Burgos Villegas; Nelson Tapia Ponce (American Journal of Potato Research, 2021)
In the Bolivian Andean region, a diversity native potatoes species ( Solanum spp) are cultivated. Areas where many types of native potato are grown are known as microcentres of potato genetic diversity. However, yields are low in these places, apparently related to viral infections. The incidence of the potato-affecting viruses Potato Virus X (PVX), Potato Virus Y (PVY), Potato Leaf Roll Virus (PLRV), Andean Potato Latent Virus (APLV) and Andean Potato Mottle Virus (APMoV) was examined by DAS-ELISA in microcentres of two high Andean regions of Bolivia, i.e. an Aymara culture region in the north of La Paz, and a Quechua culture region in the Dept. of Cochabamba. The relationship between viral incidence and potato yield was explored as well. The presence of all five viruses was detected in both regions, except APMoV in the Aymara region. The mean overall incidence of viral infection was greater in the Aymara than in the Quechua region. The most commonly detected viruses were PVX, PVY and APLV. Mix-infections of PVY + PVX and PVY + PLRV were most common in the Aymara region, and PVX + APLV and PVX + APMoV in the Quechua region. Potato yield was less in Aymara than in Quechua region and it was correlated to higher incidence of PVY and PVX in Aymara region. Low yields and high incidence of viral infection seems to be related to the ancestral management by planting native seed potatoes of poor quality. In conclusion, four of the five viruses sought were detected in the Aymara region, and all five in the Quechua region, although the overall incidence of viral infection was greater in the Aymara region, where the yields recorded were also lower. Resumen. En la región andina boliviana se cultivan una diversidad de especies nativas de papa ( Solanum spp ). Las áreas donde se cultivan muchos tipos de papa nativa se conocen como microcentros de diversidad genética de la papa. Sin embargo, los rendimientos son bajos en estos lugares, aparentemente relacionados con infecciones virales. Se examinó la incidencia de los virus que afectan a la papa, el Virus X de la Papa (PVX), Virus Y de la Papa (PVY), Virus del Rollo de hoja de Papa (PLRV), Virus Latente de la Papa Andina (APLV) y Virus moteado de la Papa Andina(APMoV) por DAS-ELISA en microcentros de dos regiones altoandinas de Bolivia, por ejemplo, una región de cultivo Aymara en el norte de La Paz y una región de cultivo Quechua en el Departamento de Cochabamba. También se exploró la relación entre la incidencia viral y el rendimiento de la papa. Se detectó la presencia de los cinco virus en ambas regiones, excepto APMoV en la región Aymara. La incidencia global media de infección viral fue mayor en la región Aymara que en la región Quechua. Los virus más comúnmente detectados fueron PVX, PVY y APLV. Las infecciones por mezcla de PVY + PVX y PVY + PLRV fueron más comunes en la región Aymara, y PVX + APLV y PVX + APMoV en la región Quechua. El rendimiento de papa fue menor enAaymara que en la región Quechua y se correlacionó con una mayor incidencia de PVY y PVX en la región Aymara. Estamos evidenciando que los bajos rendimientos y la alta incidencia de infección viral parecen estar relacionados con el manejo ancestral mediante la siembra de papas de semilla nativa de mala calidad. En conclusión, cuatro de los cinco virus buscados se detectaron en la región Aymara, y los cinco en la región Quechua, aunque la incidencia general de infección viral fue mayor en la región Aymara, donde los rendimientos registrados también fueron menores.